2013
DOI: 10.4172/2161-0487.1000129
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health, Stigmatising Beliefs, Barriers to Care and Help-Seeking in a Non-Deployed Sample of UK Army Personnel

Abstract: Introduction: Stigmatising beliefs about seeking help for mental health problems and perceived barriers to care (stigma/BTC) are commonplace among military personnel; how they influence help-seeking is unclear.Aim: To explore the role of stigma/BTC in mental health help-seeking among British Army personnel. Method: Randomly selected non-deployed personnel were assessed by questionnaire for mental health and alcohol use status, stigma/BTC levels, help-seeking and mental health related perceptions.Results: The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…In a notable exception, Jones et al found that stigma concerns did not account for military medical treatment-seeking in military personnel; however, seeking help from friends was associated with greater stigma concerns. 7 Recent studies have identified that other attitudes may need to be considered. For example, in the US National Comorbidity Survey, 8 the most commonly endorsed reason for not seeking treatment was 'Wanted to handle problem on own', or a preference for self-reliance or self-management.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a notable exception, Jones et al found that stigma concerns did not account for military medical treatment-seeking in military personnel; however, seeking help from friends was associated with greater stigma concerns. 7 Recent studies have identified that other attitudes may need to be considered. For example, in the US National Comorbidity Survey, 8 the most commonly endorsed reason for not seeking treatment was 'Wanted to handle problem on own', or a preference for self-reliance or self-management.…”
mentioning
confidence: 99%
“…In a notable exception, Jones et al found that stigma concerns did not account for military medical treatment-seeking in military personnel; however, seeking help from friends was associated with greater stigma concerns. 7…”
mentioning
confidence: 99%
“…An understanding of armed forces culture is particularly important as due to the social norms associated with mental health and alcohol use in the armed forces, personnel often do not seek help (Jones et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is cited in the literature, where it has been suggested that family members may fear adverse consequences (eg, negative occupational and social outcomes) of seeking help 16. Family members of service personnel with mental health diagnoses may be more likely to seek help if they are offered systematic reassurance from support service providers regarding their feared, adverse consequences of help-seeking 16…”
Section: Discussionmentioning
confidence: 97%